Constraints for Investors towards Nepalese Mutual Fund - Dhungel, Shuvatara; Sharma, Atul; Khatri, Krishna; Pandey, Tripty; Bashyal, Swetashma (New Perspective: Journal of Business and Economics, 2023)
This study aims to evaluate mutual fund investment behavior in the context of the Nepalese mutual fund market. While there have been countless articles exploring the effects of different factors on mutual fund investment behavior of investors, no research has been found in the context of Nepal. The study intends to analyze the relationship of mutual fund awareness level, return perception, country governance, advertisement’s relevance, fund manager’s qualities, and ease of investment towards mutual fund investment behavior. The study found that among the six factors, four factors, namely awareness level, return perception, fund manager’s qualities, and ease of investment, significantly affect mutual fund investment behavior. The relationship has been measured using different statistical tools like regression and correlation. However, country governance factors and advertisement’s relevance show no relationship with mutual fund investment behavior. This study is significant because it fills the gap in the literature on mutual fund investment behavior in Nepal. The findings of this study can help investors, fund managers, and policymakers to make informed decisions regarding mutual fund investment.